2016
DOI: 10.1002/app.44079
|View full text |Cite
|
Sign up to set email alerts
|

Continuous dosing of fast initiator during vinyl chloride suspension polymerization: Polymerization rate and PVC properties

Abstract: Continuous dosing of a fast initiator during the suspension polymerization of vinyl chloride has been carried out in a pilot-scale reactor. The kinetics course of this polymerization and the particle features of the resulting grains were discussed and compared to the conventional polymerization with the same conversion and maximum reaction rate. It was found for the system used that a suitable dosage trajectory allows the reaction rate to remain constant during polymerization. This decreases the polymerization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 48 publications
2
17
0
Order By: Relevance
“…As mentioned above, due to changing in operational conditions, all these strategies, particularly continuous initiator dosage system, can affect thermal and process behavior of the PVC resins. As published in our previous works, the continuous dosages of the fast initiator strongly affect the kinetic course of polymerization and morphological and molecular characteristics of PVC products . It was found that continuous dosages of the fast initiator during polymerization decreases the total polymerization time significantly (up to 53%), while the molecular weight distribution and molecular weight of PVC resin decreased slightly.…”
Section: Introductionsupporting
confidence: 51%
“…As mentioned above, due to changing in operational conditions, all these strategies, particularly continuous initiator dosage system, can affect thermal and process behavior of the PVC resins. As published in our previous works, the continuous dosages of the fast initiator strongly affect the kinetic course of polymerization and morphological and molecular characteristics of PVC products . It was found that continuous dosages of the fast initiator during polymerization decreases the total polymerization time significantly (up to 53%), while the molecular weight distribution and molecular weight of PVC resin decreased slightly.…”
Section: Introductionsupporting
confidence: 51%
“…On the other hand, although most performances are excellent, there are some defects in the production and application of PVC, such as a bad thermal stability, a weak resistance to light, heat, and impact, difficult processing for rigid PVC, and unstable plasticization of flexible PVC. 3,4 Therefore, modification is required to improve the quality of PVC products and develop their applications. The improvement of the photothermal stability is an important direction for the modification of PVC.…”
Section: Introductionmentioning
confidence: 99%
“…Poly(vinyl chloride) (PVC) is one of the most common commodity plastics in the world, which has been widely used in the building construction, packaging fields, automobile, aerospace, coating, and lamination industries, etc., because of its low cost, good processability, easy method of preparation, excellent chemical and fire resistance, etc. Suspension polymerization is used for the commercial production of approximately 80% of the world's PVC . The quality of suspension PVC is primarily characterized by the morphologic characteristics of the polymer particles, such as particle shape, particle size distribution, particle porosity, pore size distribution, and accessibility of the internal pores.…”
Section: Introductionmentioning
confidence: 99%
“…Suspension polymerization is used for the commercial production of approximately 80% of the world's PVC. [7][8][9] The quality of suspension PVC is primarily characterized by the morphologic characteristics of the polymer particles, such as particle shape, particle size distribution, particle porosity, pore size distribution, and accessibility of the internal pores. Notably, its handling, processing, and application are dramatically influenced by these characteristics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation